2018
DOI: 10.1186/s12967-018-1622-4
|View full text |Cite
|
Sign up to set email alerts
|

Invasive non-typhoidal Salmonella in sickle cell disease in Africa: is increased gut permeability the missing link?

Abstract: Non-typhoidal Salmonella usually induces self-limiting gastroenteritis. However, in many parts of Africa, especially in individuals who are malnourished, infected with malaria, or have sickle cell disease, the organism causes serious and potentially fatal systemic infections. Since the portal of entry of non-typhoidal Salmonella into the systemic circulation is by way of the intestine, we argue that an increased gut permeability plays a vital role in the initiation of invasive non-typhoidal Salmonella in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 63 publications
1
18
1
1
Order By: Relevance
“…This "typhoid fever-like" scenario would be in line with the clinical presentation of invasive NTS infections in sSA, i.e. febrile systemic fever with non-specific clinical features, without gastroenteritis [13] but with increased gut permeability driven by Plasmodium falciparum sequestration and altered gut microbiota associated with malnutrition [42,43].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This "typhoid fever-like" scenario would be in line with the clinical presentation of invasive NTS infections in sSA, i.e. febrile systemic fever with non-specific clinical features, without gastroenteritis [13] but with increased gut permeability driven by Plasmodium falciparum sequestration and altered gut microbiota associated with malnutrition [42,43].…”
Section: Discussionsupporting
confidence: 52%
“…e . febrile systemic fever with non-specific clinical features, without gastroenteritis [ 13 ] but with increased gut permeability driven by Plasmodium falciparum sequestration and altered gut microbiota associated with malnutrition [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…iNTS disease is caused mainly by S. Typhimurium, S. Enteritidis, and S. Dublin [8]. The iNTS disease burden in Africa is especially caused due to urbanization with large populations living in crowded and insanitary conditions with poor access to potable water [62][63][64]. iNTS is more common amongst people with an impaired immunity, and typically represents a febrile systemic illness and lower respiratory tract disease, commonly attributable to co-infections with HIV or malaria [50,60,65,66].…”
Section: Origin Classification and Diseases Caused By Salmonellamentioning
confidence: 99%
“…In addition, as for all organ systems, the gut can be damaged in children with sickle cell disease through vasculopathic processes that include recurrent hypoxiareperfusion injury induced by vaso-occlusive crises (VOC), which could also lead to reduced nutrient absorptive capacity. Recent studies suggest that VOCs initiate a cascade of interconnected changes in the gut that include enterocyte injury and apoptosis, local inflammation and immune activation, disruption of tight junction integrity, and an altered population and function of gut microbiota [8,9]. On the background of this pathophysiological complexity, the analysis by Islam, which reported that the association of SCD with anthropometric indices was significantly and strongly mediated by haemoglobin levels, should be interpreted with some caution [5].…”
Section: Nutritional Status and Sickle Cell Diseasementioning
confidence: 99%